Intelligent Industrial Design System Based on Spatial Digital Technology - Yingbin Jian; Yunpeng Li; Lijie Wang; Shenghuan Dong (Advances in Multimedia)
In order to improve the effect of intelligent industrial design, this paper combines the spatial digital technology to construct the system structure of the intelligent industrial design community. Considering the existence of the identification diffusion angle, this paper analyzes the refraction of light when it enters the workpiece and lists the calculation methods of the refraction angle of different media. Moreover, considering that the various conditions of the workpiece detection surface will make the calculation of the refraction of the identification light more complicated; this paper analyzes the specific parameters of the identification light, which lays a theoretical foundation for the accurate calculation of the subsequent wavefront arc. In addition, this paper studies defect reconstruction methods based on circle, ellipse, and polygon models. Finally, through experimental research, this paper verifies that the intelligent industrial design system based on spatial digital technology has a good effect in industrial design and can effectively improve the intelligence of modern industrial design.